This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Summer 2007 STAT333 Summary of generating function The purpose of this part is twofolds. First, given a sequence of real numbers { a n } n =0 , how to calculate the generating function A ( s ). Secondly, given the generating function A ( s ), how to find the coecients { a n } n =0 . Generating function: definition Given a sequence of real numbers { a , a 1 , . . . , a n } = { a n } n =0 , define the power series, A ( s ) = a + a 1 s + a 2 s 2 + = n =0 a n s n for every real number s for which the above power series converges. Obviously whether or not the power series converges at a particular s depends on the coecients { a n } n =0 . Every power series does exactly one of the following three things: (a) A ( s ) converges only for s = 0 (not our interest). (b) A ( s ) converges when  s  < R and diverges when  s  > R . In this case, R is called the convergence radius for the power series. (c) A ( s ) converges for all the real s (corresponds to the case R = ). In the last two cases, we call A ( s ) the generating function of the sequence { a n } n =0 . For the generating function, the close form for A ( s ) and the radius are both very important. When you find the close form, please do not forget the convergence radius. Examples of the commonly used generating functions (a) Geometric: A ( s ) = s k 1 s = n = k s n with radius R = 1. Here a n = 0 for n = 0 , 1 , . . . , k 1 and a n = 1 for n k. (b) Alternate Geometric: A ( s ) = ( 1) k s k 1+ s = n = k ( 1) n s n with radius R = 1. Here a n = 0 for n = 0 , 1 , . . . , k 1 and a n = ( 1) n for n k. (For the first two formulas, try to understand how you can get them by the formula for geometric series. In general, it is First term 1 common ratio .) (c) Exponential: A ( s ) = e s = n =0 s n n ! with radius R = . Here a n = 1 /n ! , for n = 0 , 1 , 2 . . . . (Try to under the above formula from n =0 s n e s n ! = 1. That is, the summation of the pmf of Poisson distribution is equal to 1.) 1 (d) Binomial: A ( s ) = (1 + s ) a = n =0 ( a n ) s n with radius R = 1. Here a n = ( a n ) , for n = 0 , 1 , 2 . . . ....
View
Full
Document
 Fall '10
 MenZhongxian
 Probability

Click to edit the document details